Taxonomic revision and identification keys for the giant honey bees - Kitnya, Nyaton; Brockmann, Axel; Otis, Gard W. (Frontiers in Bee Science, 2024)
The taxonomy and phylogeny of the giant honey bees (Apis; subgenus Megapis) are still controversial and unresolved. The species boundaries within the subgenus are unclear and some species that are recognized on the basis of genetic differences lack supporting morphological characters. Two species are now well accepted: Apis dorsata Fabricius, 1793, of tropical regions of Asia and Apis laboriosa Smith, 1871, that inhabits the foothills of Himalaya and neighboring mountain ranges. In addition, researchers have suggested that the two allopatric populations of giant honey bees that inhabit Sulawesi, Indonesia (A. binghami Cockerell, 1906) and the oceanic Philippine islands (A. breviligula Maa, 1953) as well as the South Indian form also deserve species status. We conducted a taxonomic study based on morphological characters of Megapis from throughout Asia. Our study confirms that Apis laboriosa is a distinct species based on numerous morphological characters. Moreover, A.